Analisis Kebutuhan Bahasa Indonesia IPTEK Siswa MAK Madrasah Aliyah Negeri 1 Jember Tahun Pelajaran 2003-2004: Needs Analysis of Indonesian Language for Science and Technology (IPTEK) Among Religious Senior High School (MAK) Students at Madrasah Aliyah Negeri 1 Jember in the 2003/2004 Academic Year - Abd. Rahman Ds (Fenomena, 2004)
Indonesian language instruction for science and technology remains teacher-centered, neglecting students' characteristics, interests, and needs. This study aims to describe the needs of Indonesian for Science and Technology among MAK students at MAN I Jember during the 2003-2004 academic year. Using a quantitative descriptive survey design, this research employed questionnaires as the main instrument, with a population of 88 students from grades I, II, and III. The findings reveal that all students need Indonesian for Science and Technology, with 71.25% stating it is very necessary. The most needed language skill is listening (51.25%), followed by speaking (22.50%). The preferred teaching method is a combination of lectures, discussions, assignments, and question-and-answer sessions (53.75%). The main learning constraints are inadequate resources and facilities (36.25%) and an imbalance between time allocation and materials (35%). Students prefer instruction twice a week, 90 minutes per session, scheduled at the beginning of school hours. This study recommends improving teacher competence in training listening, speaking, and writing skills, as well as providing adequate learning facilities. Pembelajaran bahasa Indonesia sebagai sarana pengembangan ilmu pengetahuan dan teknologi masih cenderung berpusat pada guru sehingga kurang memperhatikan karakteristik, minat, dan kebutuhan siswa. Penelitian ini bertujuan mendeskripsikan kebutuhan bahasa Indonesia IPTEK siswa MAK MAN I Jember tahun ajaran 2003-2004. Penelitian deskriptif kuantitatif dengan desain survei ini menggunakan kuesioner sebagai instrumen utama, dengan populasi 88 siswa kelas I, II, dan III. Hasil penelitian menunjukkan bahwa seluruh siswa membutuhkan bahasa Indonesia IPTEK, dengan 71,25% menyatakan sangat perlu. Aspek keterampilan yang paling dibutuhkan adalah menyimak (51,25%), diikuti berbicara (22,50%). Metode pembelajaran yang paling disukai adalah gabungan ceramah, diskusi, penugasan, dan tanya jawab (53,75%). Kendala utama pembelajaran adalah kurangnya sumber dan fasilitas (36,25%) serta ketidakseimbangan alokasi waktu dengan materi (35%). Siswa menginginkan pembelajaran dua kali pertemuan per minggu masing-masing 90 menit pada jam awal. Penelitian ini merekomendasikan peningkatan kompetensi guru dalam melatih keterampilan menyimak, berbicara, dan menulis, serta penyediaan fasilitas pembelajaran yang memadai.